In AABC, C= then prove that
cos^2A + cos^2 B - cosAcosB = 3/4
Attachments:
![](https://hi-static.z-dn.net/files/ddd/e77d8d926cc3bd5f10ce8e8c48ef6dc9.jpg)
Answers
Answered by
2
Answer:
given
C = 2π/3
now
A + B + C = π
A + B = π - C = π - 2π/3 = π/3
A = π/3 - B
applying cos
cosA = cos(π/3 - B)
cosA = cosπ/3*cosB + sinπ/3*sinB
cosA = (cosB)/2 + (√3/2)sinB
2cosA - cosB = √3sinB
squaring both side
4cos^2A + cos^2B - 4 cosAcosB = 3sin^2B
4cos^2A + cos^2B - 4cosAcosB = 3 -3cos^2B
4cos^2A + 4cos^2B - 4cosAcosB = 3
4(cos^2A + cos^2B - cosAcosB) = 3
cos^2A + cos^2B - cosAcosB = 3/4
Similar questions
Political Science,
5 months ago
Physics,
5 months ago
Economy,
10 months ago
Computer Science,
10 months ago
English,
1 year ago